Smells good enough to eat: Dimethyl sulfide (DMS) enhances copepod ingestion of microplastics. (January 2019) - Procter, Jade; Hopkins, Frances E.; Fileman, Elaine S.; Lindeque, Penelope K.
Abstract: Marine copepods have been shown to readily ingest microplastics - a crucial first step in the transfer of plastics into the marine food chain. Copepods have also been shown to elicit a foraging behavioural response to the presence of olfactory stimuli, such as dimethyl sulfide (DMS) – a volatile compound produced by their algal prey. Here, we show that the temperate Calanoid copepod Calanus helgolandicus displays enhanced grazing rates of between 0.7 and 3-fold (72%–292%) on microplastics that have been infused in a DMS solution, compared to DMS-free controls. Environmental exposure of microplastics may result in the development of an olfactory signature that includes algal-derived compounds such as DMS. Our study provides evidence that copepods, which are known to use chemosensory mechanisms to identify and locate dense sources of palatable prey, may be at an increased risk of plastic ingestion if it mimics the scent of their prey. Highlights: We show that the temperate Calanoid copepod Calanus helgolandicus displays enhanced grazing rates of between 0.7 and 3-fold (72%–292%) on microplastics that have been infused in a DMS solution, compared to DMS-free controls. Environmental exposure of microplastics may result in the development of an olfactory signature that includes algal-derived compounds such as DMS. Copepods may be at an increased risk of plastic ingestion if it mimics the scent of their prey.